Educational technology based on skill in learning era of 21 century - Arief, Zainal Abidin (Ibn Khaldun Journal of Social Science, 2019)
In the perspective of instruction educational technology based on skill in this 21 century going together the ability of higher order thinking included creation activities, evaluation, and analysis, those were different with the problem that faced by human being on the previous period. Therefore, human quality needs to be enhanced so that able to confront and overcome a variety of problems and challenge in life. The raising of human quality only can be able to acquire through quality educational process. The quality educational process constitute either one of study in educational technology study field, where it could facilitate of learning so that achieving the result of learning which maximal by employing a variety of learning resource potential optimally. The potency of students’ knowledge can be benefitted by learning technology in augmenting and producing quality graduate and having competitiveness with ability of higher level thinking. To get the high quality graduate, its need the instrument through utilization of human resource development. A technology that emphasize on the effort neither of rising of human Performance, rather individually nor in organization scale. In this case, it is a technology which effort the raising of students’ Performance, educational Performance or learning designer and improvement of the institution.